Implementation of Environmental Education Through Adiwiyata Mandiri Program in Vocational High School 1 Boyolangu Tulungagung - Hartiningtyas, Lativa; Nurmalasari, Riana (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Currently, there are many environmental damages caused by human activities. Environmental damage can cause harm to humans, for example, floods, landslides, and air and water pollution, which are examples of environmental damage caused by human activity. Education is one of the means to raise awareness for students to preserve their environment. The government seeks to apply environmental insights through formal education. One of the government programs in environmentally sound education is the Adiwiyata Program. The purpose of this study was to determine the application of environmental education at SMK Negeri 1 Boyolangu to get the Adiwiyata Mandiri award. This study used a qualitative approach with one type of case study site. Data collection techniques used interviews, observation, and documentation. The results of the study were an explanation of the application of environmental education at SMK Negeri 1 Boyolangu to get the Adiwiyata Mandiri award, a description of the steps taken by the school to anticipate obstacles to the implementation of environmental education, and exposure to the efforts made by schools in maintaining these achievements and always developing students' awareness to protect the environment.